CT and radiographic evaluation of bronchial collapsibility at forced expiration in asymptomatic brachycephalic dogs. Issue 2 (2nd January 2020) - Yoon, Hyounglok; Yu, Jin; An, Gayeon; Bang, Sohyun; Kwon, Dohoon; Kim, Hyunryung; Lee, Hanbin; Chang, Jinhwa; Chang, Dongwoo
Abstract: Bronchial collapse due to bronchomalacia is an important cause of chronic coughing in dogs. Radiographic and CT evidence of bronchial collapse has previously been reported in healthy Beagle dogs under forced expiration. However, published studies in brachycephalic dog breeds that are prone to bronchial collapse are currently lacking. In the present prospective analytical experimental study, CT and radiography were used to measure the bronchial diameter and collapsibility of each pulmonary bronchus during end‐expiratory, 5 mL/kg forced‐expiratory, and 10 mL/kg forced‐expiratory phases in 17 asymptomatic brachycephalic dogs and six healthy Beagle dogs. Bronchial collapsibility was significantly greater during forced expiration, than that at the end of expiration in both groups ( P < .001). Bronchial collapsibility measurements of the left lung lobes and the right cranial, middle, and accessory lobes were significantly higher in asymptomatic brachycephalic dogs than those in healthy Beagle dogs, during all expiratory phases ( P < .05). The higher bronchial collapsibility of brachycephalic dogs was also supported using CT multiplanar reconstruction images and radiography. In conclusion, radiographic and CT measures of bronchial collapsibility in asymptomatic brachycephalic dogs are higher than measures in healthy Beagle dogs. Therefore, measures of bronchial collapse in brachycephalic dogs should not be evaluated using the same baseline measures as those used for healthy Beagle dogs.